The Youth and Primacy against Religious Radicalism through the Organization of Mahasiswa Ahlith Thariqah Al Mu‘tabarah An Nahdliyyah (MATAN) in Indonesia - Zulfan Taufik (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2019)
In Indonesia, tariqa has become a choice to counter and fight against the radical groups that target youngsters as prey. An obvious example is the organization of Mahasiswa Ahlith Thariqah Al Mu‘tabarah An Nahdliyyah (MATAN). By employing the phenomenological approach, this study considered MATAN as a Muslim youth organization that strongly emphasizes radicalism and positivism among youngsters, especially college students. Also, it maintained that MATAN has strived to synergize intellectuality and spirituality among the students, with claims of loyalty to the preservation of moderate, tolerant, inclusive, and consistent Islam. This preservation concerns sharī‘ah, ḥaqīqah, and ma‘rifah, and simultaneously maintains awareness as an integral part of Indonesian people living in the country. Therefore, they must obey the country’s rules imbued with Pancasila and the 1945 Constitution. These points can inspire every activity of the members of MATAN to actively promote and engage themselves in de-radicalization efforts. Meanwhile, the findings confirmed several studies and surveys conducted in Morocco, Algeria, and Mali, asserting that the tariqa has become a new fondness and is believed to be a savior of youngsters from religious extremism.